Partitioning of the Open Waters of the Gulf of Mexico Based on the Seasonal and Interannual Variability of Chlorophyll Concentration. Issue 4 (13th April 2018) - Damien, Pierre; Pasqueron de Fommervault, Orens; Sheinbaum, Julio; Jouanno, Julien; Camacho‐Ibar, Victor F.; Duteil, Olaf
Abstract: The seasonal and interannual variability of chlorophyll in the Gulf of Mexico open waters is studied using a three‐dimensional coupled physical‐biogeochemical model. A 5 years hindcast driven by realistic open‐boundary conditions, atmospheric forcings, and freshwater discharges from rivers is performed. The use of recent in situ observations allowed an in‐depth evaluation of the model nutrient and chlorophyll seasonal distributions, including the chlorophyll vertical structure. We find that different chlorophyll patterns of temporal variability coexist in the deep basin which thereby cannot be considered as a homogeneous region with respect to chlorophyll dynamics. A partitioning of the Gulf of Mexico open waters based on the winter chlorophyll concentration increase is then proposed. This partition is basically explained by the amount of nutrients injected into the euphotic layer which is highly constrained by the dynamic of the winter mixed layer. The seasonal and interannual variability appears to be affected by the variability of atmospheric fluxes and mesoscale dynamics (Loop Current eddies in particular). Finally, estimates of primary production in the deep basin are provided. Key Points: Good agreement between the GOLFO12‐PISCES model and observational data set Partition of the Gulf of Mexico open waters in three biogeochemical regions based on the seasonal variability of the chlorophyll distribution Chlorophyll variability is driven by the relative position of the mixed layer depth and the nitracline depth